(3Yed ef WH def MHs - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb GdEfSGf ef fWaI CeTGL jfbSe gPG GdcJGH Edi LRFjf , CMOgeG JYOjO GdGeQGV ef QCS Edi bOe , eGYOG eG jJYdb HGdRjfI s
(3BNQgG (B:s
(3eHJhQI hBNQ GdehLhO ajgG (B: (3GdaUd GdKGfj ai GdYV , hajg YV GdcdH hZjQ GdcdH , hYV GdEfSGf s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B162 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs